IMPROVING STUDENT’S READING COMPREHENSION BY USING THINK PAIR SHARE TECHNIQUE - Jamaliah, Mustakim Sagita, Ratna Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2020)
The objective of the study is to find out whether teaching reading by using think pair share technique cooperative learning can improve student’s reading comprehension. This study was conducted at second years students of SMAN 1 Kembang Tanjong, pidie. The writer used Think Pair Share Technique to teach the student in reading comprehension. The instrument used to collect data in this research was a set of test, that consisted of pretest and posttest. Pretest was given before the writer doing treatment by using Think Pair Share Technique to know the ability of student in mastering reading skill. Post-test was given to know the ability of the student after the teaching proses by used Think Pair Share Technique for six times. The calculation of the data showed the average score of pre-test experimental class was 53,8 and control class was 47,4. Whereas value of post-test in experimental class was 63.73 and control class was 48,36. The writer got t-score of the students is 5,17 which higher than t-table 1,684 by the level significant of 5%. It indicated that there was a significance progression between students’ pre-test and post-test score in the experimental class after applying Think Pair Share Technique. So, the students’ who was taught reading skill by using think pair share technique were better than whose did not taught reading by using Think Pair Share Technique.Key Words: Reading, Think Pair Share, Cooperative Learning